Answer:
![z\left(-6.4\:-3.5x\right)=-6.4z-3.5zx](https://tex.z-dn.net/?f=z%5Cleft%28-6.4%5C%3A-3.5x%5Cright%29%3D-6.4z-3.5zx)
Hence, Option 'C' is true.
Step-by-step explanation:
Given the expression
![z\left(-6.4\:-3.5x\right)](https://tex.z-dn.net/?f=z%5Cleft%28-6.4%5C%3A-3.5x%5Cright%29)
Apply distributive law: ![a\left(b-c\right)=ab-ac](https://tex.z-dn.net/?f=a%5Cleft%28b-c%5Cright%29%3Dab-ac)
Here: ![a=z,\:b=-6.4,\:c=3.5x](https://tex.z-dn.net/?f=a%3Dz%2C%5C%3Ab%3D-6.4%2C%5C%3Ac%3D3.5x)
so the expression becomes
![z\left(-6.4\:-3.5x\right)=z\left(-6.4\right)-z\cdot \:\:3.5x](https://tex.z-dn.net/?f=z%5Cleft%28-6.4%5C%3A-3.5x%5Cright%29%3Dz%5Cleft%28-6.4%5Cright%29-z%5Ccdot%20%5C%3A%5C%3A3.5x)
∵ ![+\left(-a\right)=-a](https://tex.z-dn.net/?f=%2B%5Cleft%28-a%5Cright%29%3D-a)
Therefore,
![z\left(-6.4\:-3.5x\right)=-6.4z-3.5zx](https://tex.z-dn.net/?f=z%5Cleft%28-6.4%5C%3A-3.5x%5Cright%29%3D-6.4z-3.5zx)
Hence, option 'C' is true.
(y2-y1)/(x2-x1)
(-7-5)/(4-2)
-12/2= -6
P is (18, -16)
to find the answer, u would solve it in reverse order of the midpoint formula by first doing the x-values:
5(2)= 10-(-8) = 18
and then the same to y-values:
-10(2)= (-20)-(-4) = -16
to get:
(18, -16)
Answer: $2244.76
Step-by-step explanation:
Well, <em>semimonthly </em>means that she is paid the amount of $1,122.38 twice a month. I am making the assumption that taxes have already been taken out of this amount, and the amount listed above is how much she will take home. I then multiplied $1,122.38 × 2 which equaled $2244.76. This is how much Genelle will take home monthly.
Answer:
Step-by-step explanation
Let's say d = distance, r = speed and t = time
We know the distance formula is :
distance = speed x time
d = r multiplied by t
d = rt
If the speed is 15km/hr, the time would be 30 minutes shorter.
Since d = rt,
90 = 15t
t = 6,
This means the time taken for the bus to complete the journey at 15km/hr would be 6hrs.
Originally though, the journey takes 30 minutes longer.
So we can say t = 6.5 hrs , and we know d = 90
Now we use the distance formula:
d = rt, since we want to find the original speed, we want to find r.
Speed = distance/time
r = d/t
r = 90/6.5
r = 180/13
Therefore the original speed is 180/13 km/hr